Delayed Return: Consolidation of the Zimbabwean Diaspora and Transnationalism - Rose Jaji (REMHU: Revista Interdisciplinar da Mobilidade Humana, 2021)
Abstract. This article discusses consolidation of the Zimbabwean diaspora and its transnational activities. It presents formation of this particular diaspora as an unanticipated development that is contingent upon circumstances as they evolve in both sending and receiving countries. It draws from longitudinal research with Zimbabwean migrants in Germany and South Africa to illustrate this argument. It also borrows from Tsuda’s transnational outcome framework to provide a nuanced understanding of Zimbabwean migrants’ varied relationships with both Zimbabwe and the receiving countries. The article argues that migrants’ decision to settle for the long-term in the receiving country is not always made at the same time as the decision to migrate itself or in the initial stages of life in the receiving country. There are many cases among Zimbabwean migrants showing that migration was initially perceived as quest for reprieve from the country’s economic and political challenges while they “waited” for the situation to improve. However, the crisis in Zimbabwe has dragged on for more than two decades with no tangible solution in sight thus transforming waiting into settling. Economic and political factors in Zimbabwe as well as factors in the receiving countries influenced the formation and consolidation of the Zimbabwean diaspora and its transnational activities. Diaspora formation and consolidation in this case is an outcome of migrants’ adaptation of their initial plans to new realities obtaining in both the sending and receiving countries.